Soil-transmitted helminth infections and nutritional indices among Filipino schoolchildren. - Mary Lorraine S Mationg; Gail M Williams; Veronica L Tallo; Remigio M Olveda; Eindra Aung; Portia Alday; Mark Donald Reñosa; Chona Mae Daga; Jhoys Landicho; Maria Paz Demonteverde; Eunice Diane Santos; Thea Andrea Bravo; et al. (Public Library of Science (PLoS), 2021)
Background Soil-transmitted helminth (STH) infections are still prevalent among schoolchildren in the Philippines. We evaluated the risk factors associated with STH and the relationship between STH and nutritional indices among schoolchildren aged 9-10 years in Laguna province, the Philippines. Methods We used the baseline data from 40 schools enrolled in a randomised controlled trial of the Magic Glasses Philippines health education package. Data on demographic and socio-economic variables, and STH related knowledge, attitudes and practices, were obtained through a questionnaire. Stool samples were collected and assessed for STH egg presence using the Kato-Katz technique. Haemoglobin levels and height and weight of study participants were also determined. The generalized estimating equations approach was used to construct logistic regression models to assess STH-associated risk factors, and the association between any STH infection and anaemia, child stunting, wasting and being underweight. The trial is registered with the Australian New Zealand Clinical Trials Registry (ACTRN12616000508471). Findings Among 1,689 schoolchildren, the prevalence of any STH was 23%. The prevalence of anaemia, stunting, being underweight and wasting was 13%, 20.2%, 19% and 9.5%, respectively. Age, socio-economic status, rural/urban classification of schools and knowledge of STH were significant risk factors for acquiring a STH infection. Moreover, infections with any STH were significantly associated with stunting (P = <0.001) and being underweight (P = <0.003), but not wasting (P = 0.375) or anaemia (P = 0.462) after controlling for confounding covariates. Conclusion The study findings emphasise the need for sustainable deworming in tandem with other measures such as the provision of health education, improvements in sanitation and hygiene, and nutritional programs in order to control STH infections and improve morbidity outcomes in schoolchildren. Trial registration Australian New Zealand Clinical Trials Registry (ACTRN12616000508471).